INTEGRATED APPROACH TO THE DEVELOPMENT OF THE FINANCIAL-CREDIT SYSTEM AND IMPROVEMENT OF LIVING STANDARDS IN CENTRAL ASIA - Olimov Abror (Scholar Express Journals, 2025)
The development of the financial-credit system and the improvement of the population’s standard of living are among the key priorities for sustainable growth in Central Asia, particularly in the Republic of Uzbekistan. This article examines the interconnection between financial system reforms, socio-economic development, and innovations that enhance living standards. The paper analyzes existing problems in the financial-credit system, evaluates its impact on economic stability and social welfare, and explores strategies for digital transformation, education, healthcare, and environmental sustainability. Practical policy recommendations and innovative approaches are presented to ensure inclusive economic development and improve the quality of life in the region
Keywords: financial-credit system; Uzbekistan; Central Asia